Hox transcription factors: an overview of multi-step regulators of gene expression - Carnesecchi, Julie; Pinto, Pedro; Lohmann, Ingrid (The international journal of developmental biology, 2018)
Hox transcription factors (TFs) function as key determinants in the specification of cell fates during development. They do so by triggering entire morphogenetic cascades through the activation of specific target genes. In contrast to their fundamental role in development, the molecular mechanisms employed by Hox TFs are still poorly understood. In recent years, a new picture has emerged regarding the function of Hox proteins in gene regulation. Initial studies have primarily focused on understanding how Hox TFs recognize and bind specific enhancers to activate defined Hox targets. However, genome-wide studies on the interactions and dynamics of Hox proteins have revealed a more elaborate function of the Hox factors. It is now known that Hox proteins are involved in several steps of gene expression with potential regulatory functions in the modification of the chromatin landscape and its accessibility, recognition and activation of specific cis-regulatory modules, assembly and activation of promoter transcription complexes and mRNA processing. In the coming years, the characterization of the molecular activity of Hox TFs in these mechanisms will greatly contribute to our general understanding of Hox activity.